AN ANALYSIS ON TRANSLATION TECHNIQUES IN THE SUBTITLE OF THE MOVIE “5 CM” - OLENKA, FONDA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Translation, Translation Technique, Subtitle, Movie. Translating is not an easy task because it deals with transferring thoughts and ideas from one language to another. The knowledge of the culture of both languages and the knowledge of the texts being translated and target readers play a very important role when it comes to making a good translation. Therefore to avoid literal translation, possible misunderstandings, and inaccuracies, it is not enough for a translator to have an excellent knowledge of both languages but also that of their culture. This study examines the translation techniques used to translate the subtitle of the movie “5 CM”. There are two problems to be solved in the study, namely: (1) what translation techniques used by the translator; (2) what techniques mostly used by the translator in translating the subtitle of the movie “5 CM”.This is a qualitative research which is conducted descriptively. The data were thedialogues and the subtitle of “5 CM” movie, Indonesian and English versions. The data were analyzed by identifying the techniques proposed by Nida.The results of the study revealed that the techniques applied by the translator involved: addition, subtraction, and alteration. There were 94 sentences that are used as the data. Addition was applied in several ways, for example by adding “to be”: is, am, and were. Subtraction was also applied in several ways, for example subtraction of information or words. Alteration was applied in the case of changing some word classes to another. And from the result of analysis in 94 sentences, the writer discovered that translation technique of addition which were found in the 44 sentences was mostly used by the translator when doing the translation.The thesis only covers the translation techniques in the subtitle of the movie “5 CM”.There are other areas of translation that can be used as the focus of the study. Therefore, to have a complete picture of the translation of the subtitle of the movie “5 CM” other researchers are suggested to make other studies about this, such as the translation method, translation procedure and other areas of translation.